The application of Multi-objective Harris Hawks Optimization in many-objective optimal power flow - Cai, Junfeng; Ai, Xinyu; Zhang, Jingrui (Chinese Automation Congress (Online), 2022)
The vigorous development of heuristic algorithms has promoted their application in various engineering problems. In view of the modern power system's requirements that multiple optimization factors should be considered simultaneously, this paper firstly establishes a many-objective optimal power flow (Ma-OPF) model that considers up to 5 optimization objectives. Then, a newly proposed heuristic algorithm, named Harris Hawks Optimization (HHO), is improved as a multi-objective HHO (MO-HHO) combined with an elimination mechanism for solving the proposed model. The simulation results of several algorithms in the IEEE 30-bus system validate that the proposed MO-HHO is superior to other considered algorithms in solving Ma-OPF problems.